Smart Chicken Farm Monitoring System - Ali, Mohamad Lokman; Munirah Ab. Rahman; Nik Shahidah Afifi Md Taujuddin (Evolution in Electrical and Electronic Engineering, 2020)
Recently, the using of smart technology are common working process in various  field such as agriculture, traffic light and medical. In the process of poultry farming in the world, rapid development of technology has been built such as closed poultry farming equipped with technological systems and more to smart farming system due to the high demand for chicken broiler all over the world including Malaysia. As a consequence, many new poultry farmers have ventured into this field. However, many of them suffer from problems such as chicken diseases due to the unconducive environment of chicken coop. Unsuitable temperature and humidity in chicken coop may lead the chicken susceptible to disease such as Coryza which causes chicken eyes become swollen and loss appetite. Therefore, a system named Smart Chicken Farm Monitoring System has been developed to monitor and control the environment of chicken coop by using sensors and Internet of Thing (IoT) platform. With this system, poultry farmers can monitor and control the temperature and humidity in the coop using DHT11 automatically. Poultry farmers can also estimate the weight of chickens by using the load cell sensor to identify the maturity of chicken broilers in the coop. This system is believed may help chicken farmers in monitoring a conducive chicken coop and the growth of the chicken broiler.